Spousal Cognitive Status and Risk for Declining Cognitive Function and Dementia: The Atherosclerosis Risk in Communities Study - Lee, Mark; Demmer, Ryan T.; Kucharska-Newton, Anna; Windham, Beverly Gwen; Palta, Priya; Shippee, Tetyana; Lutsey, Pamela L. (Journal of aging and health, 2023)
Objectives: We investigated the relationship between the cognitive status of participants’ spouses and participants’ own cognitive outcomes, controlling for mid-life factors. Methods: Participants (n = 1845; baseline age 66–90 years) from the prospective Atherosclerosis Risk in Communities Study were followed from 2011 to 2019. We used linear regression and Cox proportional hazard models to estimate whether spouses of people with MCI/dementia had lower cognitive functioning and elevated risk of incident dementia. Results: Having a spouse with MCI/dementia was associated with a deficit in cognitive function (b = −0.09 standard deviations; 95% CI = −0.18, 0.00). Adjustment for mid-life risk factors attenuated this association (b = −0.02 standard deviations; 95% CI = −0.10, 0.06). We observed no significant relationship between spousal MCI/dementia status and incident dementia (hazard ratio = 0.97; 95% CI = 0.69, 1.38). Discussion: Spousal cognitive status is not associated with poor cognitive outcomes independent of mid-life factors.